THE URGENCY OF ANTI-CORRUPTION EDUCATION TO REALIZE A CORRUPTION-FREE FUTURE - Faridah, Ida; Maspul, Kurniawan Arif; Rozak, Abdur; Nursidik, Nursidik; Amalia, Fina (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This research discusses the importance of anti-corruption education in creating a future free from corruption. Anti-corruption education is considered as one of the strategies for eradicating corruption because it can create an anti-corruption cultural ecosystem in building the character of the younger generation. Higher education has an important role in instilling the value of integrity through the Tri Dharma of Higher Education which includes education, research, and community service. Anti-corruption education also has a damaging impact, such as damaging markets, prices and fair business competition, undermining the law, reducing the quality of life and sustainable development, undermining the democratic process, violating human rights, and causing other crimes to develop. Therefore, all levels of society are expected to participate in eradicating corruption. This research also examines anti-corruption education as character building that emphasizes free will and individual behavior through potential. Anti-corruption education not only teaches what is right and what is wrong, but also involves character building and humanism in higher education.